THE LEADERSHIP EFFECT ON THE JOB SATISFACTION AND DISCIPLINE WHICH IMPACT ON EMPLOYEE PERFORMANCE - Sutianingsih, . (PEOPLE: International Journal of Social Sciences, 2018)
The purpose of this study is to provide analyze the influence of job satisfaction on leadership, discipline, employee performance, and analyze the influence of job satisfaction and discipline on employee performance. hypothesis proposed: leadership has a positive and significant influence on job statisfaction, discipline, and performance, and job satisfaction and discipline have a significant positive effect on employee performance.This research is a survey research. The population is employees of manufacturing companies in the Surakarta city. The samples are 83 people. The primaries are the data used the data collected through the distribution of questionnaires to employees. The data obtained were tested by validity test, reliability test, classic assumption test, regression analysis, F Test, t test, and determination analysis.Conclusion: Leadership has a positive and significant impact on job statisfaction, discipline, and performance. Job satisfaction and discipline have a significant positive effect on employee performance. Based on path analysis it is known that: the direct effect of leadership variables on performance is smaller when compared with the result of the indirect influence of leadership through job satisfaction on performance. The result of the direct influence of leadership variables on performance is smaller when compared with the result of the indirect influence of leadership through discipline to performance.